Surface treatment with condensed phosphates reduced efflorescence formation on dry fermented sausages with alginate casings. (December 2019) - Hilbig, Jonas; Murugesan, Vinothkumar; Gibis, Monika; Herrmann, Kurt; Weiss, Jochen
Abstract: The effect of a phosphate surface treatment on dry-fermented sausages with co-extruded alginate casings was investigated to reduce or inhibit the formation of white efflorescences on the surface of the sausages. Furthermore, with the co-extrusion process a continuous sausage production is possible with increased product volume compared to batch processing. Moreover, the production of meat snack products with very small diameters are possible. Solutions (5%) of different commercially available phosphates, mixture of di- and polyphosphates and two polyphosphates, were applied to the surfaces of the sausages after drying. The area amount of efflorescence was reduced from ∼65% on the control to 4–7%, depending on the phosphates used. The migration of magnesium and lactate to the surface of the sausage was inhibited by the diffusion of free phosphates and calcium phosphate complexes from the surface layer into the sausage. This study illustrated an easy application to prevent efflorescence formation. Graphical abstract: Image 1045495 Highlights: The surface treatment inhibited or reduced the transport of magnesium and lactate to the surface. The content of calcium and phosphate on the surface decreased during storage. The phosphate surface treatment inhibited the efflorescence formation.